Discovering Romans : content, interpretation, reception - Thiselton, Anthony C. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
This third volume in the Discovering Biblical Texts series offers readers a compact, up-to-date, and student-friendly introduction to Paul's letter to the Romans, focusing on its structure, content, theological concerns, key interpretive debates, and historical reception. Anthony C. Thiselton alerts readers to key issues and questions raised by the text, encouraging in-depth study and a sincere grappling with the theological and historical questions raised by this often-controversial epistle. He pays special attention to the book's reception and its influence on Christian history and culture, exploring and explaining the approaches and conclusions of a wide range of ancient and modern interpreters.
Why read Romans? Eight brief reasons -- Strategies of interpretation : three essential strategies for Romans -- Nine further strategies often useful for parts of Romans -- The reception history of Romans -- The textual criticism and integrity of Romans -- Paul, traveller and citizen of Rome -- Paul introduces himself and the theme of the Gospel (1.1-17) -- The Gentile world is judged and alienated from God (1.18-32) -- The Jewish world as moral critic (2.1-3.8) --Judgement and grace on all : redemption and atonement (3.9-31) -- The promise of the covenant God : trust, the test case of Abraham (4.1-25) -- Peace with God (5.1-11) -- Christ and Adam : humanity and the new humanity (5.12-21) -- Dead to sin : alive to God (6.1-23) -- Free from the condemnation of the law (7.1-25) -- Life characterized by the Holy Spirit's indwelling (8.1-17) -- The renewal of all things : suffering and future glory (8.18-39) -- Israel's unbelief : filling a gap in Paul's argument (9.1-29) -- God's faithfulness and Israel's responsibility (9.30-10.21) -- The salvation of "all Israel" (11.1-36) -- The outworking of the Christian life : sacrifice and worship (12.1-21) -- Christian obligations (13.1-14) -- Mutual welcome and respect : "the strong" and "the weak" (14.1-15.13) -- Paul's travel plans and the coming missionary task (15.14-16.2) -- Final greetings, final appeal and doxology (16.3-27).
Originally published: London : SPCK, 2016.
Includes bibliographical references (pages 264-278) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc